Feeding styles and adiposity in children of 6 months- 5 years of age: Protocol for a systematic review and meta- analysis. - Divya Nair Haridas; Onno C P van Schayck; Giridhar R Babu; N Sreekumaran Nair; Prafulla Shriyan (PLoS ONE)
Obesity in children is a major public health concern due to the increased risk of developing adverse health outcomes in their future, and disability in adulthood. The existing systematic reviews on the topic are limited in scope, focusing solely on high-income countries and children aged 4-12 years. Hence, we propose to conduct a systematic review and meta-analysis to understand, how exposure to authoritative feeding style versus authoritarian, indulgent, uninvolved compare in terms of its association with adiposity in children aged 6 months to 5 years. Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines were followed for ensuring the completeness of the protocol. Case-control and cohort studies will be included. Searches will be done using electronic databases viz. PubMed, Ovid EMBASE, PsycINFO and Web of Science. Grey literature will be searched using OpenGrey and Grey Literature Report. We will only include quantitative studies using the developed search strategy. For categorical outcomes, relative risks, odds ratios, and hazard ratios with confidence intervals and for continuous outcomes mean difference with confidence intervals will be used. Risk of Bias In Non-randomized Studies- of Exposure (ROBINS-E) will be used for the evaluation of risk of bias in the individual observational studies. Considering the inherent variability in the observational studies, random effects meta-analysis will also be conducted. If between-study heterogeneity exists, a subgroup analysis based on low and middle-income countries vs. high income countries will be conducted. If the data is not suitable for combining quantitatively, a narrative synthesis will be undertaken. We propose to identify publication bias by using contour-enhanced funnel plots and "trim and fill" method. Outcome reporting bias will be ascertained by comparing the outcomes published in the protocol and the published report. The Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) system will be used to understand the confidence we can have on the effect estimates. Registration: This protocol has been registered in International Prospective Register of Systematic Reviews (PROSPERO) on 13 March 2023 with registration number CRD42023356014.